The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s42255-022-00587-9
|View full text |Cite
|
Sign up to set email alerts
|

Food-seeking behavior is triggered by skin ultraviolet exposure in males

Abstract: Sexual dimorphisms are responsible for profound metabolic differences in health and behavior. Whether males and females react differently to environmental cues, such as solar ultraviolet (UV) exposure, is unknown. Here we show that solar exposure induces food-seeking behavior, food intake, and food-seeking behavior and food intake in men, but not in women, through epidemiological evidence of approximately 3,000 individuals throughout the year. In mice, UVB exposure leads to increased food-seeking behavior, foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 95 publications
4
22
1
Order By: Relevance
“…A recent epidemiology study reported that midday solar ultraviolet (UV) exposure (between 1100 h and 1300 h) increased food-seeking behavior and food intake in men but not in women. A similar finding of weight gain was observed solely in male mice [ 115 ]. These properties of light affecting peripheral regions of the body in a sex-dependent manner emphasize the importance of understanding the influence of light on individual organs.…”
Section: Properties Of Light Affecting Metabolismsupporting
confidence: 84%
“…A recent epidemiology study reported that midday solar ultraviolet (UV) exposure (between 1100 h and 1300 h) increased food-seeking behavior and food intake in men but not in women. A similar finding of weight gain was observed solely in male mice [ 115 ]. These properties of light affecting peripheral regions of the body in a sex-dependent manner emphasize the importance of understanding the influence of light on individual organs.…”
Section: Properties Of Light Affecting Metabolismsupporting
confidence: 84%
“…Allemann et al [41] reported that UVR (alone) did not significantly affect food intake and adiposity. However, Parikh et al [42] found that prolonged UVB exposure (50 mJ/cm 2 ) increased food-seeking behavior and food intake exclusively in mice and human men via p53-mediated ghrelin. This process is inhibited in females due to estrogen interfering with UV-induced p53.…”
Section: Obesitymentioning
confidence: 99%
“…740,741 As already mentioned, there are several proven benefits: a bit of daily sun exposure increases lifespan substantially; 25 approximately 90% of all vitamin D used in our body is formed through the action of sun exposure; 26 a few minutes of sun exposure can lower the blood pressure for hours; 23 exposure to VL stimulates opsin that modulates the activity of cells from the subcutaneous white adipose tissue; 742 UV-B stimulates food-seeking behavior and food intake in men, but not in women. 743 The use of sun blockers avoids both the ancillary benefits of UV-B exposure and the erythema reaction, which is a natural protection mechanism that was selected during human evolution to avoid the consequences of an excess of sun exposure. 744 Switching off this signal allows people to endure longer times of sun exposure, with consequences that have not been properly investigated.…”
Section: Scenarios For Sun Protectionmentioning
confidence: 99%
“…Unfortunately, besides the poor efficacy of protection there are intrinsic conceptual problems with the current sun protection guidance. First, the sun protection strategies contemplate mainly the bad consequences of an excess of sun exposure, imposing widespread and unrestricted use of sun blockers, without considering the benefits of small sun exposures. , As already mentioned, there are several proven benefits: a bit of daily sun exposure increases lifespan substantially; approximately 90% of all vitamin D used in our body is formed through the action of sun exposure; a few minutes of sun exposure can lower the blood pressure for hours; exposure to VL stimulates opsin that modulates the activity of cells from the subcutaneous white adipose tissue; UV-B stimulates food-seeking behavior and food intake in men, but not in women …”
Section: Scenarios For Sun Protectionmentioning
confidence: 99%